THE APPLICATION OF INTERACTIVE TECHNOLOGIES FOR TEACHING MATHEMATICAL MODELING TO STUDENTS - Sokolov, Viktor; Kostylev, Denis; Smirnova, Zhanna; Makeeva, Anastasiya; Peteraitis, Sergey (Revista Inclusiones, 2020)
The relevance of the research issue is due to the organization of the educational process based on the contemporary techniques for teaching, in particular, interactive technologies. The concept of “interactive education technologies” has assumed particular significance. It is more than just a process of interaction between a teacher and a student; it is a new stage of the educational process. In the current system of teaching mathematics to students of non-mathematical specialties, in particular future teachers of chemistry, there are a number of negative trends, among which the formalization of mathematical knowledge should be observed. The article aims at considering the use of interactive technologies in teaching mathematical modeling in educational institutions. The leading approach to the study of this issue is the main function of interactive learning capable of revealing the effective use of interactive technologies in the educational process. The key findings of the study is the solution to the problem of information and communication technologies in teaching mathematical modeling, through which students can demonstrate the improved results of their activities in the educational process of the university. The main results are indicators of interactive forms –a group work, including the work in small groups.